Analyzing Success Factors in Developing Mobile Applications for Farmers in Thailand Using Analytic Hierarchy Process Technique - Kunlerd, Attapol; Nabumroong, Boonlueo; Jantarakomet, Kraisak; Ruttanaprasert, Ruttanachira; Burana, Kunlachat (IAES Indonesian Section, 2024)
This study applies the Analytic Hierarchy Process (AHP) as a robust decision-making framework to address critical gaps in risk management and criteria prioritization within mobile application development for the agricultural sector, specifically focusing on Thai rice farmers. The research identifies essential factors influencing technology adoption through input collected from 100 rice farmers in Surin Province. Using AHP, these factors were systematically ranked, with